2011
DOI: 10.1111/j.1365-2141.2011.08915.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding of Langerhans cell histiocytosis

Abstract: Summary Langerhans cell histiocytosis (LCH) is a proliferative disease of cells that share phenotypic characteristics with the primary antigen presenting cells of the epidermis. Its clinical manifestations are highly variable, extending from very benign forms to a disseminated, aggressive disease that causes significant mortality. Although many of the fundamental pathogenetic features of LCH have been enigmatic, recent advances have led to a much clearer understanding of the disease. In particular, careful mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 97 publications
2
86
0
3
Order By: Relevance
“…LCH and ECD have a shared history of controversy regarding whether they are reactive, inflammatory conditions or clonal, neoplastic diseases. 2,3 Recent studies, however, found that 57% of LCH cases and 54% of ECD patients harbored BRAF V600E mutation in the diseased tissue, strongly suggesting a neoplastic etiology in most cases. 4,5 Haroche et al have tested the notion that the BRAF V600E acts as a so-called "driver mutation" of these diseases by treating 3 patients with refractory ECD, 2 of whom had coincident LCH, with vemurafenib, which was recently approved for use in patients with metastatic melanoma characterized by BRAF V600E mutation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LCH and ECD have a shared history of controversy regarding whether they are reactive, inflammatory conditions or clonal, neoplastic diseases. 2,3 Recent studies, however, found that 57% of LCH cases and 54% of ECD patients harbored BRAF V600E mutation in the diseased tissue, strongly suggesting a neoplastic etiology in most cases. 4,5 Haroche et al have tested the notion that the BRAF V600E acts as a so-called "driver mutation" of these diseases by treating 3 patients with refractory ECD, 2 of whom had coincident LCH, with vemurafenib, which was recently approved for use in patients with metastatic melanoma characterized by BRAF V600E mutation.…”
mentioning
confidence: 99%
“…At present, the best-established treatment of ECD is interferon and standard therapies of LCH use cytotoxic agents. 3,10 Thus, a targeted treatment approach not only adds a new element to the therapeutic armamentarium, but offers the possibility of less-toxic treatments; in the case series, vemurafenib at the ultimate treatment dose was quite well tolerated. Although the response duration remains unproven, there is also hope that ECD and LCH, which appear to be cytogenetically less complex than metastatic melanoma, might develop resistance at a lower rate and that BRAF inhibitors, whether vemurafenib or others, could result in long-term responses.…”
mentioning
confidence: 99%
“…It was originally described as a nonneoplastic process and reported under different names including: inflammatory myofibroblastic tumor, plasma cell granuloma, xanthomatous pseudotumor, pseudosarcomatous, fibromyxoid tumor and inflammatory myofibrohistiocytic proliferation in the literature subsequently [7,8]. IP primarily affecting the central nervous system is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Typical accumulation of histiocytes, electron microscopic observation of Birbeck granules and the presence of Langerhans' cell-associated markers, including cluster of differentiation (CD)1a and S-100 protein, are crucial for establishing a diagnosis of LCH (6). LCH is typically considered to be an extremely rare disease of childhood, with an incidence rate of ~2-5/1,000,000 children/year (7). There are no specific signs and symptoms associated with LCH involving the skull, and the most common presentation is a painful and immobile scalp mass, which may be palpable in certain cases (5,8).…”
Section: Introductionmentioning
confidence: 99%